'Fair and square': what do students think about the ethnicity degree awarding gap?. Issue 8 (14th September 2021) - Wong, Billy; ElMorally, Reham; Copsey-Blake, Meggie
ABSTRACT: In UK higher education, minority ethnic students are less likely to graduate with a good degree than their White British counterparts, even when prior attainment is considered. Until recently, concerns about this ethnicity degree awarding gap have not received the research attention it deserves. In this paper, we contribute to this gap in knowledge with a focus on how students make sense of the difference in degree outcomes by ethnicity. Informed by 69 in-depth interviews with minority and majority ethnic students at a UK university, we explore their views towards the ethnicity degree awarding gap, why it exists and what would be their solution to reduce this difference. Although some students perceived the awarding gap as a reflection of individual aptitude, others have attributed social barriers for degree outcome differences. We present five recommendations as suggested by students for policy and practice. Firstly, the provision of greater economic support for minority ethnic students, which will improve access and a more diverse student population. Secondly, to establish an institutional commitment to challenge and eradicate all forms of racism on campus, including microaggressions. Thirdly, to increase representation of minority ethnic staff and students in higher education to improve students' sense of belongings and aspirations, with the emphasis on greater staff diversity. Fourthly, to diversify the curriculum with a wider range of values and perspectives incorporated into teaching. Finally, universities need to be proactive and reflective to ensure structural barriers are reduced or eliminated through additional support or alternative provisions.